2020
DOI: 10.1186/s40359-020-00435-z
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of parenting stress in mothers of preterm infants during their first-year home

Abstract: Background: Maternal stress following the birth of an infant is well acknowledged. It is particularly so when infants are born prematurely as their mothers cannot fully take on their parenting role until their infant(s) is discharged from neonatal intensive care units (NICUs). In this exploratory study, we examined whether these mothers' parenting stress would lessen during their first-year reunification with their infant(s) as they settle into motherhood at home. Methods: Two groups of mothers with infants bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…One of the ways to support the parents and reduce their stress is family-centered care; nurses have a key role in providing it successfully [ 5 ]. Parental support promotes proper parent–child interaction and improves the attachment process [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to support the parents and reduce their stress is family-centered care; nurses have a key role in providing it successfully [ 5 ]. Parental support promotes proper parent–child interaction and improves the attachment process [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to identify therapeutic interventions aimed at alleviating possible stress symptoms in the infants ( Kobus et al, 2021a ) and their mothers, thereby promoting a positive mother–child relationship ( Benzies et al, 2013 ). Research has shown that targeted interventions such as music therapy can help and support mothers of preterm infants to establish positive parenting routines that are beneficial for themselves and their babies ( Lau et al, 2020 ). Music therapy is an individualized and family-integrated therapy approach ( Haslbeck and Bassler, 2020 ), offering various benefits for preterm infants and their parents ( Ettenberger et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the sustained increase in the survival of preterm infants over the last three decades, parental stress following the birth of a child is undeniable. This is evidenced by the extensive research literature in this domain be they in reviews or studies focused on particular infant’s characteristics, parental distress, e.g., depression, anxiety, or imbalanced family situations ( 10 27 ). Of interest, studies have shown how such parental stress responses may be associated with a particular condition observed in their infant(s).…”
Section: Introductionmentioning
confidence: 99%
“…At present, studies on maternal stress in NICU have focused primarily on alleviating recognized psychological issues such as depression, anxiety ( 17 , 27 , 45 , 47 , 48 ). However, as interactions between multiple stressors may further impact behaviors and maternal mental health, our understanding of the “overall” stress experienced by mothers and the current support we offer is incomplete.…”
Section: Introductionmentioning
confidence: 99%